Writing for journalists - Swaine, Matt; Gilbert, Harriett, 1948-; Allen, Gavin L. (New York: Routledge, 2022)
"Thoroughly revised and updated, the fourth edition of Writing for Journalists focuses on the craft of journalistic writing, offering invaluable insight on how to hook readers and keep them to the end of your article. The book offers a systematic approach to news and feature writing that starts with the basics and builds to more complex and longer pieces. The authors give the reader the tools they need to deliver engaging and authoritative writing that works across print and digital. Drawing on professional insight from writers across the industry, the book guides readers through the essential elements needed to write powerful and effective news stories, from hard news pieces to features on business, science, travel, and entertainment reviews. New to this edition are hands-on writing exercises accompanying each chapter to help reinforce key points; chapters on how to build a professional profile, pitch stories and get commissioned; and a section on online writing, SEO, analytics and writing for social media. This is an essential guide for all journalism students and early-career journalists. It also has much to offer established journalists looking to develop their writing and lead editorial teams"--
Includes index.
Keywords: Journalism -- Authorship